The role of the entry-and-stretch phase at the different paces of race in front crawl swimming - Samson, M.; Monnet, T.; Bernard, A.; Lacouture, P.; David, L. (Journal of Sports Sciences, 2015)
The aim of this study was to determine the role played by the entry-and-stretch phase in the coordination of swimming, at the different paces of race. Three national level swimmers (two men and one woman) were recorded, in lateral and bottom views, in three swimming paces: sprint (50 m and 100 m), middle-distance (200 m and 400 m) and long-distance (800 m and 1500 m). Anatomical landmark positions were obtained by manual digitalisation of the videos. Computational fluid dynamics and experimental studies (with a strain gauge balance and particle image velocimetry method) were used to measure and to calculate the external forces applied to the hand and to the forearm and to visualise the flow around the profile. Entry-and-stretch is the phase which varies the most according to the swimming pace. This phase can be decomposed into two sub-phases: one, the extension forward coordinated with the insweep of the opposite arm, and another one, the rotation downward coordinated with the upsweep. Results show that, at the three paces, this phase is not propulsive and could contribute essentially to maintain the horizontal balance of the body.